2016
DOI: 10.48550/arxiv.1605.06098
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chaos in AdS$_2$ holography

Kristan Jensen

Abstract: We revisit AdS2 holography with the Sachdev-Ye-Kitaev models in mind. Our main result is to rewrite a generic theory of gravity near an AdS2 throat as a novel hydrodynamics coupled to the correlation functions of a conformal quantum mechanics. This gives a prescription for the computation of n-point functions in the dual quantum mechanics. We thereby find that the dual is maximally chaotic.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
293
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(301 citation statements)
references
References 22 publications
8
293
0
Order By: Relevance
“…8 To the best of our knowledge this relation is still unproven for Schwarzschild black holes. 9 With the constraint that we are only interested in states that evolve to the same thermal state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 To the best of our knowledge this relation is still unproven for Schwarzschild black holes. 9 With the constraint that we are only interested in states that evolve to the same thermal state.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years OTOCs and these exponents, encoding the speed with which quantum systems scramble information, received much attention [9][10][11][12][13][14][15], especially after it was shown that there exists an upper bound [1] for λ OTOC ≤ 2πT and thus an upper bound on the speed of the development of quantum chaos. Furthermore, systems that are holographic duals to Einstein gravity have been found to saturate this bound [1,5,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to be clear about the problem that we want to address, we need to recall some aspects of the SYK model. In particular, it is well known that the infrared theory in the strong coupling limit is described by hydrodynamics [66]. In § 3.1, we first briefly review the model.…”
Section: The Modelmentioning
confidence: 99%
“…The path integral in the JT gravity on Riemann surfaces with asymptotic boundaries is obtained by computing the path integral over the wiggles along the asymptotic boundaries of the surfaces [30,31,32], together with the path integral over the moduli of the Riemann surfaces with the geodesic boundaries and the path integral over the "trumpets" connecting an asymptotic boundary (with which a boundary wiggle is associated) and a geodesic boundary [8]. The volume of the moduli of hyperbolic Riemann surfaces with geodesic boundaries is known as the "Weil-Petersson volume.…”
Section: Introductionmentioning
confidence: 99%